2022
DOI: 10.21203/rs.3.rs-2099763/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between serum calcium level and in-hospital mortality in patients with acute myocardial infarction: a retrospective cohort study

Abstract: The association between serum calcium levels and the prognosis of patients with acute myocardial infarction (AMI) remains controversial. This study aimed to explore the association between serum calcium and in-hospital mortality in patients with AMI. A total of 7284 patients were eventually enrolled in this study, of which 799 (10.97%) died during hospitalization. For each patient, serum calcium, corrected to albumin, was calculated and categorized into four groups: Q1 ≤8.5, Q2 8.5-9.5, Q3 9.5-10.5, and Q4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…Acute stroke patients have also been documented to exhibit both hypocalcemia and hypercalcemia. A study indicated that hypocalcemia was present in 11.8% of acute ischemic strokes and was linked to a greater probability of hemorrhagic transformation [5]. Hypercalcemia has also been observed in acute stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…Acute stroke patients have also been documented to exhibit both hypocalcemia and hypercalcemia. A study indicated that hypocalcemia was present in 11.8% of acute ischemic strokes and was linked to a greater probability of hemorrhagic transformation [5]. Hypercalcemia has also been observed in acute stroke patients.…”
Section: Introductionmentioning
confidence: 99%